(untitled) (Confluências | Revista Interdisciplinar de Sociologia e Direito, 2014)
Sustainable development has become a major topic in the Brazilian agenda. Corporate social responsibility (CSR) has gained ground in Brazil during the last years and a group of Brazilian managers have helped to shape the paper of businesses as key players in social development. Literature has evidenced that ‘contextual factors’ shape the definition of CSR in a given environment and ‘company motivational factors’ shape its scope. Following this pattern, the understanding of CSR in Brazil will be analyzed. In particular, the categorization of CSR theories under four approaches (economic, political, integrative and ethical theories) enunciated by academia to define the relationship between enterprise and society will be used in order to describe the emergence of CSR in Brazil in the 1960s and its evolution until today.